Status Review on Gas Insulated Switchgear Partial Discharge Diagnostic Technique for Preventive Maintenance - Visa Musa Ibrahim; Zulkurnain Abdul-Malek; Nor Asiah Muhamad (Institute of Advanced Engineering and Science, 2017)
Gas insulated switchgear (GIS) plays a vital role in high voltage transmission of electrical energy due to its advantages of high reliability and performance, compact in dimensions and outstanding compatibility with the environment. It uses sulphur hexafluoride gas as its insulant and coolant because of its high dielectric strength and excellent arc quenching ability. Gas insulated switchgear in operation suffers the challenge of its insulation decomposition and eventually failure due to the activities of partial discharge that arouses from defects. This failure is catastrophic and it will lead to entire power out stage that will affect all categories of human activities, so there is a need for Gas insulated switchgear condition monitoring and diagnoses in order to carry out preventive maintenance. This paper reviews diagnostic techniques and methods for Gas insulated switchgear insulation degradation caused by partial discharge for the purpose of carrying out preventive maintenance to avert its failure.